Creative IDEA: Introducing a Statewide Art Therapy in Prisons Program - Soape, Evie (International journal of offender therapy and comparative criminology, 2022)
Education is regarded as an avenue for success while the under-educated are disproportionately more likely to be incarcerated and remain within the correctional system. Current prison reforms have focused on increasing access to educational programming. However, these programs are not designed to address the lack of control, poor self-regulation, low emotional intelligence, inadequate social skills, or lack of internal motivation that hinder progress. Art therapy has been found effective in mitigating these impediments. Recognizing this, a partnership arose between a state Department of Corrections and a State University’s graduate art therapy program out of which emerged an Art Therapy in Prisons Program, funded through the Individuals with Disabilities Education Act. Two art therapists provided services to youthful male and female offenders in four institutions to assuage these obstacles. This article explores the genesis and development of this program, and the flexible adjustments required to address the impending COVID-19. We conclude how those who participated did indeed demonstrate improvement.